1998
DOI: 10.1007/bf02499163
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies similar to antidifferentiation ones in immune neutropenias

Abstract: Two groups were distinguished among patients with autoimmune neutropenia with manifest antigranulocytic antibodies. One group consisted of patients whose sera reacted with all forms of leukocytes (granulocytes, monocytes, T and B lymphocytes), like CD45 monoclonal antibodies. Sera of patients from the other group reacted only with polymorphonuclear leukocytes and monocytes, similarly as CD13 monoclonal antibodies. Immunologically distinguished types of neutropenia were characterized by a typical chronic or acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
1

Year Published

1998
1998
1998
1998

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
2
1
Order By: Relevance
“…Complement-dependent cytotoxic antibodies reacting with allogeneic and autologous polymorphonuclear leukocytes are strongly expressed in such patients, particularly in children. Our studies showed that in contrast to aUoimmune neutropenias of newborns, the sera of patients with autoimmune neutropenias react with the leukocytes of the mother, father, and nonrelatives [14,41]. A high inverse correlation was noted between the titer of granulocytotoxic antibodies and the absolute count of polymorphonuclear leukocytes in the patient's blood.…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…Complement-dependent cytotoxic antibodies reacting with allogeneic and autologous polymorphonuclear leukocytes are strongly expressed in such patients, particularly in children. Our studies showed that in contrast to aUoimmune neutropenias of newborns, the sera of patients with autoimmune neutropenias react with the leukocytes of the mother, father, and nonrelatives [14,41]. A high inverse correlation was noted between the titer of granulocytotoxic antibodies and the absolute count of polymorphonuclear leukocytes in the patient's blood.…”
contrasting
confidence: 57%
“…A high inverse correlation was noted between the titer of granulocytotoxic antibodies and the absolute count of polymorphonuclear leukocytes in the patient's blood. These data indicate that autosensitization to antibodies of polymorphonuclear leukocytes is caused not only by drug therapy, playing the role of a peculiar adjuvant, but by certain genetic prerequisites as well [14]. The fact that one of the parents of a child with immune neutropenia often had autogranulocytic antibodies is one more piece of evidence in favor of this hypothesis.…”
mentioning
confidence: 93%
“…In some cases the recipient's erythrocytes are completely replaced by donor's antigenic phenotype, involving the alteration of recipient's blood group. In other cases both autologous erythrocytes and the donor phenotype erythrocytes circulate in the organism [1,5].…”
mentioning
confidence: 98%